PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK OPPO PADA MAHASISWA UNIVERSITAS HKBP NOMMENSEN MEDAN (STUDI KASUS) - TRI MELDA MEI LIANA (LP2MTBM MAKARIOZ, 2018)
Thid study aim to analyze the influence of Advertising and Brand Image on Buying Desicion of the student ofMedan Nommensen HKBP University. Research variable include : Buying Desicion (Y) as the dependent variable,Advertising (X1) as the independent variable, and Brand Image (X2) as the independent variable. This study adoptedthe Marketing Management theory, as it pertaining to the Advertising, Brand Image, and Buying Decision.The method of data analysis uses is the multiple regression analysis. The population of this study are all studentof Medan Nommensen HKBP University generation 2013 and the sample taken are 50 respondents.The first hypothesis finding shows the Advertising have no influences significantly on the Buying Decision of the studentof Medan Nommensen HKBP University. The second hypothesis shows that the Brand Image influences significantlyon the Buying Decision. The third hypothesis shows that the Advertising and Brand Image simultaneously influencesignificantly on the Buying Interest of the student of Medan Nommensen HKBP University.